Efeito da concentração de dopante e da temperatura de calcinação na termometria luminescente do vanadato de ítrio (YVO4) dopado com íons terras raras (Er3+, Nd3+) - Tavares, Francisca Jusciele Ribeiro (2022)
In this dissertation, the effects of dopants concentration and calcination temperature on yttrium vanadate (YVO4) doped with Er3+ and Nd3+ were investigated. To produce the samples, the modified sol-gel method was used. Structural characterization was performed using X-ray diffraction technique (XRD) and optical characterization by photoluminescence measurements. The XRD results showed that the method used was quite efficient to obtain the desired compounds with a single phase. The materials produced were evaluated as luminescent thermometers inside biological windows I and II. For luminescent thermometry, the emission spectra were collected at different temperatures, while the samples were excited with a CW laser at 660 nm. Luminescence intensity ratios (LIR) between the ratios: 802/830, 802/1002 of YVO4: Er3+, 809/914 of YVO4: Nd3+ and 809/914, 809/1002 of YVO4: Er3+ , Nd3+ were explored. In addition, relative sensitivity was also investigated. Emissions from the transitions of neodymium at ~ 810 nm (4F5/2 → 4 I9/2), ~ 914 nm (4F3/2 → 4 I9/2), and ~ 1065 nm (4F3/2 → 4 I11/2) and from erbium at ~ 820 nm (4 I9/2 → 4 I15/2) and ~ 975 nm (4 I11/2 → 4 I15/2) and new LIR schemes for thermally uncoupled levels were evaluated. The influence of calcination temperature variation and the concentration of neodymium and erbium in the host matrix for temperature sensing was investigated. Furthermore, it was found that the relative sensitivity (Sr) of pairs of thermally uncoupled levels may be associated with probable ion migrations or the cross-relaxation process, thus causing a low Sr in YVO4: Er3+ . In all cases with YVO4: Nd3+ , good sensitivities were obtained and the material co-doped with 0.5% Er3+, 1% Nd3+ was the one that obtained the best sensitivity with the value corresponding to 2.1% K-1 . The obtained results indicate that the investigated materials, as well as the proposed methodologies, are promising for thermal sensing and optical heating of deep tissues.